2013
DOI: 10.1093/ageing/aft155
|View full text |Cite
|
Sign up to set email alerts
|

REFINE (REducing Falls in In-patieNt Elderly) using bed and bedside chair pressure sensors linked to radio-pagers in acute hospital care: a randomised controlled trial

Abstract: Background: falls in hospitals are a major problem and contribute to substantial healthcare burden. Advances in sensor technology afford innovative approaches to reducing falls in acute hospital care. However, whether these are clinically effective and cost effective in the UK setting has not been evaluated.Methods: pragmatic, parallel-arm, individual randomised controlled trial of bed and bedside chair pressure sensors using radio-pagers (intervention group) compared with standard care (control group) in elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 22 publications
2
93
0
7
Order By: Relevance
“…Although conceptually attractive, the use of movement alarms (bed or chair alarms) has not been successful in reducing fall rates. 6 In common with community-based trials, more promising results are seen when the complex multiple components of risk are accounted for in assessment and managed through relevant interventions. Systematic reviews have consistently suggested that multifactorial assessments linked to appropriate interventions may reduce falls in hospital by 20-30%.…”
Section: Can Falls In Hospital Be Prevented?mentioning
confidence: 99%
“…Although conceptually attractive, the use of movement alarms (bed or chair alarms) has not been successful in reducing fall rates. 6 In common with community-based trials, more promising results are seen when the complex multiple components of risk are accounted for in assessment and managed through relevant interventions. Systematic reviews have consistently suggested that multifactorial assessments linked to appropriate interventions may reduce falls in hospital by 20-30%.…”
Section: Can Falls In Hospital Be Prevented?mentioning
confidence: 99%
“…Furthermore, recent literature suggests pressure-sensitive devices and alarms have little to no effect on fall-related events in hospitals. 16,17 In the current study, most nursing homes use similar devices and alarms, however one nursing home is currently pilot testing an alarm-free initiative, which seems to be a growing phenomenon. 18,19 …”
Section: Discussionmentioning
confidence: 91%
“…A reductionistic focus on one element of a system is insufficient to mitigate a complex adverse outcome such as a patient fall . Consequently, randomized controlled trials of individual processes such as use of bed/chair pressure sensors, low‐low beds, and patient education have not significantly decreased fall risk. Bundling multiple processes may decrease fall risk by 30 percent, but the ideal combination of processes and the most effective implementation structure remains unknown …”
Section: Introductionmentioning
confidence: 99%